Sisterhood of the Traveling Pants 2 - Hamri, Sanaa; Tamblyn, Amber; Bledel, Alexis, 1982-; Ferrera, America, 1984-; Brashares, Ann (Burbank, CA : Warner Home Video, 2008)
During the summer after their first year of college, four young women stay in touch through a shared pair of secondhand jeans that magically adapts to each of their figures and affects their attitudes to their different summer experiences.
Based on the novel "Forever in blue : the fourth summer of the sisterhood" by Ann Brashares.
Originally released as a motion picture in 2008.
Sequel to the film "Sisterhood of the traveling pants" (2005).
Features: Go jump off a cliff, additional scenes, gag reel.
Amber Tamblyn, Alexis Bledel, America Ferrera, Blake Lively.
MPAA rating: PG-13.
Keywords: Brashares, Ann -- Film and video adaptations; Teenage girls -- Drama; Female friendship -- Drama; Romance films; Film sequels; Video recordings for the hearing impaired; Fiction films; Coming of age films; Based on the book; Feature films; Comedy films